2010
DOI: 10.1101/gr.106773.110
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics, proteomics, and regulatory DNA analysis in isogenic settings using zinc finger nuclease-driven transgenesis into a safe harbor locus in the human genome

Abstract: Isogenic settings are routine in model organisms, yet remain elusive for genetic experiments on human cells. We describe the use of designed zinc finger nucleases (ZFNs) for efficient transgenesis without drug selection into the PPP1R12C gene, a “safe harbor” locus known as AAVS1. ZFNs enable targeted transgenesis at a frequency of up to 15% following transient transfection of both transformed and primary human cells, including fibroblasts and hES cells. When added to this locus, transgenes such as expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
287
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(296 citation statements)
references
References 44 publications
9
287
0
Order By: Relevance
“…Thus, insertion of exogenous DNA into the human AAVS1 locus by genome editing increases cellular contractile force even though fundamental cellular features such as cell morphology and cell growth are maintained. Previous research showed that transgene integration into the human AAVS1 locus did not change cell growth rate [13] or pluripotency [2]. Thus, the AAVS1 locus is thought to be a strong candidate for gene therapy.…”
Section: Reduction Of Mbs85 Expression Is Associated With Myosin Regumentioning
confidence: 99%
“…Thus, insertion of exogenous DNA into the human AAVS1 locus by genome editing increases cellular contractile force even though fundamental cellular features such as cell morphology and cell growth are maintained. Previous research showed that transgene integration into the human AAVS1 locus did not change cell growth rate [13] or pluripotency [2]. Thus, the AAVS1 locus is thought to be a strong candidate for gene therapy.…”
Section: Reduction Of Mbs85 Expression Is Associated With Myosin Regumentioning
confidence: 99%
“…[23][24][25] For initial validation of gRNAs designed for Cpf1, we used the reporter plasmid pCAG-EGxxFP-AAVS1, which was previously constructed to contain an approximately 500 bp genomic region of AAVS1 14) integrated into the enhanced green fluorescent protein (EGFP) coding region (Supplementary Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Transient transfection using conventional plasmids has been the predominant way to deliver these programmable nucleases into cells. 3,20,[27][28][29][30][31][32] In this study, we report that minicircle vector-mediated delivery of programmable nucleases leads to higher frequencies of target gene modification and lower cytotoxicity than delivery with a conventional plasmid, indicating that the minicircle vector is an attractive delivery method.…”
Section: Preparation Of Minicircle Dna Encoding Zfns or Talensmentioning
confidence: 97%
“…[16][17][18][19] TALEN-mediated gene targeting has also been successfully demonstrated in several systems including plants, 20,21 zebrafish, 22 yellow catfish, 23 Caenorhabditis elegans, 24 rats, 25 mice 26 and human cells. 3 To date, conventional plasmids, 3,20,[27][28][29][30][31][32] integrase-defective lentiviral vectors, 18,33 adenoviral vectors, 34,35 adeno-associated viral vectors, 36 direct microinjection into embryos, 12,[37][38][39] and recombinant proteins 40,41 have been used to deliver engineered nucleases. Among these approaches, plasmid-mediated delivery has been predominant because it is easy to generate the necessary components and vector integration into the host genome is relatively rare.…”
Section: Introductionmentioning
confidence: 99%